Physiological maturation in seeds of Lophantera lactescens Ducke - Silva, Patrícia; Alves, Edna; Araújo, Luciana; Cruz, José; da Cruz Silva, Natália (Revista Ciência Agronômica, 2019)
Lophantera lactescens Ducke (Malphigiaceae) is an arboreal plant that propagates by seed; once exclusive to the Amazon region, it is now widely distributed in South America. The aim of this work was to study the maturation process in seeds of L. lactescens, in order to determine the point of physiological maturity and the ideal time for harvesting. The field study was conducted at the Centre for Agrarian Sciences of the Federal University of Paraíba (CCA/UFPB), Campus II, in Areia, in the State of Paraíba (PB), where the fruit was harvested every two weeks over two consecutive years. The water content, external coloration, fruit size, fruit dry weight, germination and vigour (seed germination index, and seedling length and dry weight) were evaluated. The experimental design was completely randomised, with data submitted to analysis of variance and polynomial regression, as a function of the harvest time. For the two years of the study, the water content decreased during the maturation process, reaching 11% at 210 days after anthesis. Fruit dry matter increased during the process, with rises in germination and seed vigour, reaching a maximum value between 190 and 210 days after anthesis respectively. A light-brown coloration with wrinkling of the fruit pericarp is a good visual indicator for determining the point of physiological maturity of the seeds in this species. Under the environmental conditions found in Areia PB, the ideal time for harvest and the physiological maturity of the seeds of L. lactescens are reached from 165 to 186 days after anthesis.